Website-Based Wudu Interactive Learning Animation to Increase Students' Learning Enthusiasm - Setiawan, Fariz Hendra; Azano, Mario; Febriansyah, Andre Rivaldo; Muvid, Muhamad Basyrul (Universitas Al-Amien Prenduan, 2023)
Website-Based Wudu Learning Animation is an innovation in wudu learning aimed at the younger generation, especially young children. In this lesson, animation is used to clarify the ablution process and make it interesting for children so as to improve the quality of their worship. The method used is the development of a website that contains interactive animations that show the steps for ablution visually. Each step is equipped with an explanation that is easy to understand and that children can follow. The result of this development is a learning website with the name (Wudu Splash) which can be accessed by anyone and at any time online and for free. It is hoped that with this website (Wudu Splash), users can more easily understand and master the correct ablution techniques, as well as improve the quality of their worship.